Застосування нечіткої мережі NEFCIass для оцінки кредитоспроможності постачальників банків - Циба, Т. А..; Гузнак, Г. (Видавництво Національного університету «Львівська політехніка», 2009)
A possible solution of problem of estimation of phisical persons' solvency with the usage of modified NEuro-Fuzzy СLASSifier(NEFCIass) that is based on the generalized architecture of fuzzy pertseptron is offered. A short description of architecture and principle of work of the original and modified NEFCIass are examined. The practical application of the system for the estimation of phisical persons' solvency and the result of this research are shown.
Keywords: кредитоспроможність; нечіткі правила; нечіткий перцептрон; NEFCIass; функції приналежності; нечіткі множини; база правил